Energy, exergy analysis, and sustainability assessment of different engine powers for helicopter engines. Issue 13 (21st October 2017) - Yildirim, Elif; Altuntas, Onder; Mahir, Necati; Karakoc, T. Hikmet
ABSTRACT: The rapid decrease of energy resources has accelerated studies on energy efficiency. Energy efficiency refers to the effective use of energy, in other words, completing a specific task to the required standard by using less energy. Exergy is an effective instrument to indicate the effective and sustainable use of energy in systems and processes. Transportation is an important part of human life. The studies on energy saving and the effective use of energy in different areas around the world have also increased for transportation systems and vehicles. With the more effective use of fuel, there will be potential benefits for the environment as well as a reduction in operating costs. This study includes energy and exergy analyses as well as a sustainability assessment by using C8 H16 as a fuel at different engine powers (150–600 SHP (shaft horse power)), for the piston-prop helicopter engine. The maximum exergetic sustainability index was found at the power that provided the maximum energy and exergy efficiency. As a result of this index, the lowest waste exergy ratio, the lowest exergy destruction factor, and the lowest environmental impact factor were obtained. The highest exergy destruction and the highest exergy loss value were obtained at maximum power (600 SHP).